Caractéristiques d'une supervision à distance de stagiaires en enseignement en ce qui concerne la création d'un sentiment de présence - Matthieu Petit
When a teaching internship takes place abroad or in remote areas, the support offered by the university (or a higher education school) can be done without presence. Increasingly, supervisors of these internships can use a range of ICT to limit problems caused by distance, including the isolation of the learner. From qualitative and quantitative results of an exploratory-descriptive study of comprehensive nature, we identify the key features of a remote internship supervision regarding the creation of a sense of presence. According to different types of presence (teaching, cognitive and social), ICT use, the possibility of a hybrid supervision, collaboration with members in the school community, and ethical issues, these features facilitate the identification of robust actions for creating presence in internship supervision.